2015
DOI: 10.5851/kosfa.2015.35.6.824
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Processed Sulfur Supplementation on Water-holding Capacity, Color, and Lipid Profiles of Pork

Abstract: This study was performed to investigate the effect of dietary processed sulfur supplementation on water-holding capacity, color, and lipid profiles of pork according to the level of dietary processed sulfur (0%, CON; 0.3%, S). The pigs were slaughtered at an average final weight of 120 kg, and the longissimus dorsi muscles were collected from the carcasses. As results, pork processed with sulfur had significantly higher moisture and ash contents compared to those of CON but lower crude fat, pH, expressible dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…However, the PUFA/SFA ratio was not significantly different between SP and NP. Yang et al (2015) demonstrated that basal diet supplementation with 0.3% processed sulfur increased MUFA in pigs. Also, children who eat foods containing lots of MUFA have healthier serum lipid profiles (Sanchez-Bayle et al , 2009).…”
Section: Resultsmentioning
confidence: 97%
“…However, the PUFA/SFA ratio was not significantly different between SP and NP. Yang et al (2015) demonstrated that basal diet supplementation with 0.3% processed sulfur increased MUFA in pigs. Also, children who eat foods containing lots of MUFA have healthier serum lipid profiles (Sanchez-Bayle et al , 2009).…”
Section: Resultsmentioning
confidence: 97%
“…Jang et al [ 15 ] found that pH, redness and yellowness decreased but lightness increased as pigs were supplemented with dietary sulfur. Yang et al [ 36 ] also indicated that the pH value was significantly lower as well as CIE a* (redness) and CIE b* (yellowness) values and that the CIE L* (light reflection) value was higher when pigs were fed 0.1% dietary sulfur. In the present study, similar results were observed for pigs supplemented with dietary sulfur.…”
Section: Resultsmentioning
confidence: 99%
“…Yang et al [36] also indicated that the pH value was significantly lower as well as CIE a * (redness) and CIE b * (yellowness) values and that the CIE L * (light reflection) value was higher when pigs were fed 0.1% dietary sulfur. In the present study, similar results were observed for 1 ) The experimental phases were divided into four phases and every feeding phase was three weeks.…”
Section: Pork Qualitymeat Characteristicsmentioning
confidence: 98%